Promoting Collaborative Learning through Student Centered Approach with Project Work (2022)
ABSTRACT : This study is an action research project carried out with high schoolers at Institución Educativa Josefina Muñoz González; a public institution located in Rionegro, Antioquia. The aim of this project was to promote collaborative learning through project work. The actions consisted of the creation of a project, the implementation of collaborative learning in the classroom and collaborative evaluation. Data collection instruments included a teacher journal, a questionnaire, and two focus group interviews with the learners. Findings showed opportunities and challenges in collaborative learning, effectiveness of classroom routines, and increase in student participation